2001
DOI: 10.1080/09629350120054536
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary nitrite, a marker of nitric oxide, in active inflammatory bowel disease

Abstract: BACKGROUND: Nitric oxide (NO) production is increased in inflammatory bowel disease (IBD), and measurement of NO metabolites may be useful for monitoring disease activity. AIMS AND OBJECTIVES: To characterise urinary nitrite levels, a stable metabolite of NO, in IBD and to evaluate its potential as a marker of disease activity. METHODS: Twelve-hour urinary nitrites were measured by the microplate assay method in 46 patients with IBD (active; n = 32). Urinary samples from 16 healthy individuals served as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
(43 reference statements)
0
22
0
1
Order By: Relevance
“…Human and animal studies convincingly showed that NO production is up-regulated in IBD and correlates with disease activity. [21][22][23][24][25][26][27][28][29][30] In 2002, Koek et al reported that FeNO levels were elevated in IBD patients and correlated with disease activity, 28 suggesting that gastrointestinal inflammation could elevate FeNO levels. None of our patients had IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal studies convincingly showed that NO production is up-regulated in IBD and correlates with disease activity. [21][22][23][24][25][26][27][28][29][30] In 2002, Koek et al reported that FeNO levels were elevated in IBD patients and correlated with disease activity, 28 suggesting that gastrointestinal inflammation could elevate FeNO levels. None of our patients had IBD.…”
Section: Discussionmentioning
confidence: 99%
“…126 Research has also shown that nitric oxide acts as an effector of the innate immune system targeting adenoviruses and other similar viruses. 127 As a result, during acute infections we see a sudden and dramatic increase in excretion of urinary nitrite, 128 a stable metabolite of nitric oxide 129 . Fever, the body's evolutionarily conserved response to infection, is also accompanied by urinary excretion of creatinine, urea and ammonia.…”
Section: Blood Urea Nitrogen and Creatininementioning
confidence: 99%
“…При хроническом неяз-венном колите отмечено снижение концентрации NО, причем оно сочетается с интенсификацией перекисных процессов, снижением активности каталазы, что свиде-тельствует об инактивации NО вследствие повышенного образования активных форм кислорода. У больных язвен-ным колитом пул оксида азота существенно увеличен [6]. Содержание оксида азота повышено у детей с болезнью Крона и неспецифическим язвенным колитом [7].…”
Section: Introductionunclassified